Validation of 11 added items of the outpatient version of the Utrecht Symptom Diary in patients receiving chemotherapy or targeted therapy - Josephine J. Koldenhof; Bernice O. Akpobome; Danielle Zweers; Stance Klaasse; Saskia C. C. M. Teunissen; Petronella O. Witteveen; Karijn P. M. Suijkerbuijk; Alexander de Graeff; Frederieke H. van der Baan (SpringerOpen, 2024)
Abstract Introduction The Utrecht Symptom Diary (USD) is a validated Dutch patient-reported outcome measurement (PROM) tool - based on the Edmonton Symptom Assessment System - to assess and monitor symptoms in cancer patients. The USD contains 11 items concerning frequently occurring symptoms in cancer patients (pain, sleeping problems, dry mouth, dysphagia, lack of appetite, abnormal stool, nausea, shortness of breath, fatigue, anxiety and depressed mood) and an item on overall well-being. For the outpatient USD 11 items concerning frequently occurring signs and symptoms in patients receiving chemotherapy and/or targeted therapy were added to the USD: taste alteration, oral pain, weight loss, diarrhoea, hair changes, skin problems, nail problems, eye problems, tingling, concentration problems and problems with sexuality. This current study aimed to evaluate the 11 added items on this treatment specific outpatient USD in cancer patients receiving intravenous chemotherapy and/or targeted therapy. Methods Observational longitudinal retrospective cohort study including all adult outpatients with cancer receiving intravenous chemotherapy and/or targeted therapy in an academic hospital in the Netherlands who completed at least one outpatient USD as part of routine care (2012-2021). Relevance, comprehensiveness as well as criterion and construct validity were assessed. Results 1733 patients who completed ≥ 1 outpatient USD during intravenous chemotherapy and/or targeted therapy were included for analysis. Relevance as well as comprehensiveness of the items on the outpatient USD in this patient population was shown. Criterion validation was demonstrated for all added items of the outpatient USD - except for the item on oral pain. An additional analysis showed that mouth problems were detected with both outpatient USD items oral pain and dry mouth. Construct validity was demonstrated for the items hair changes and skin and nail problems. Construct validity on eye problems was not tested due to the low number of paired outpatient USDs. Conclusions The treatment specific outpatient USD is a validated PROM in outpatients with cancer receiving intravenous chemotherapy and/or targeted therapy. Considering its validity in this broad group of patients, we think the treatment-specific outpatient USD is widely applicable. In addition to providing tailored supportive symptom care, the USD-data can be used to increase knowledge about symptom burden in daily practice in this population.